The Application of Hirschberg Maxims in Frost’s ‘Mending Wall’ and Darwish’s ‘Scenario Jaahiz’ - Manaar M.A. AL-Badri; Nassier A. G. Al-Zubaidi, Phd. (مجلة الآداب, 2022)
This paper presents a study of prosodic traits and the pragmatic implications connected to them. It is suggested that there is a prosodic code in which a selection of suprasegmental elements is deliberately and consciously changed, putting it in relation to syntactic structures, lexical choices, and pragmatic meanings, is believed that a prosodic grammar works together with the linguistic and rhetorical devices in order to organize a narrative discourse firstly, and secondly to highlight the argumentative part within the narrative discourse.